Comparison of Morphometric Parameters, Nutritional Composition, and Textural Properties of Seven Crustaceans Species - Zhigang Yang; Qingqing Jiang; Wuxiao Zhang; Silei Xia; Hongyan Tian; Fei Liu; Wenping Yang; Yebing Yu; Yanmin Wu; Yongzhi Zhu; Zhiqiang Xu; Zemao Gu; et al. (Fishes, 2024)
In order to study the muscle quality of different crustaceans, we aim to provide a comprehensive assessment of their muscle quality characteristics as a theoretical reference. In this work, seven major species of farmed and consumer crustaceans were selected, including crayfish (Procambarus clarkii), freshwater prawns (Macrobrachium rosenbergii), pacific white shrimp (Litopenaeus vannamei), black tiger shrimp (Penaeus monodon), kuruma prawns (Penaeus japonicus), river prawns (Macrobranchium nipponense), and Chinese shrimp (Penaeus chinensis). Their morphometric parameters, nutritional composition, textural properties, and physical and chemical indexes were comparatively analyzed. The results showed that the meat content (MC, about 14.78%) of crayfish was significantly lower than that of the other six species. By contrast, pacific white shrimp had the highest MC, although the MCs of black tiger shrimp, kuruma prawns, and Chinese shrimp are greater than 40%. All seven crustacean species were high in protein and low in fat, while pacific white shrimp had the highest crude protein, crude lipid, and crude ash content compared to the other crustaceans. The content of threonine (Thr) was the highest in crayfish. The content of methionine (Met) and lysine (Lys) was the highest in freshwater prawns. The content of isoleucine (Ile), leucine (Leu), and non–essential amino acid (NEAA) was the highest in pacific white shrimp. C18:2n-6 (linoleic acid, LA) was the highest in freshwater prawns and pacific white shrimp; C18:3n-3 (linolenic acid, LNA), C20:4n-6 (arachidonic acid, AA), unsaturated fatty acids (UFA), and monounsaturated fatty acids (MUFA) were all the highest in crayfish; and polyunsaturated fatty acids (PUFA) was the highest in freshwater prawns, but the content was not significantly different from crayfish, pacific white shrimp, black tiger shrimp, and Chinese shrimp. Pacific white shrimp had the highest values for hardness, cohesiveness, gumminess, and chewiness. The redness values of crayfish, black tiger shrimp, and Chinese shrimp were significantly higher than those of the other three species except kuruma prawns. Compared to other crustaceans, river prawns had the highest drip loss and cooking loss. Black tiger shrimp and Chinese shrimp had the lowest cooking loss rates. The research shows that the tail muscle of the seven species of crustaceans is rich in protein, essential amino acids, unsaturated fatty acids and low in fat, representing a high-quality protein. Among these crustaceans, the main essential amino acids and essential fatty acids in the tail muscle of pacific white shrimp, freshwater prawns, and crayfish are higher in content and better in nutritional value.